2011
DOI: 10.1080/14786435.2011.586158
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation of polycrystals of Co3(Al,W) with the L12structure

Abstract: The plastic behaviour of Co 3 (Al,W) polycrystals with the L1 2 structure has been investigated in compression from 77 to 1273 K. The yield stress exhibits a rapid decrease at low temperatures (up to room temperature) followed by a plateau (up to 950 K), then it increases anomalously with temperature in a narrow temperature range between 950 and 1100 K, followed again by a rapid decrease at high temperatures. Slip is observed to occur exclusively on {111} planes at all temperatures investigated. The rapid decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…In addition, strengthening of the grain boundaries by precipitates of borides or intermetallic phases has been found to be critical to the mechanical properties of the γ 0 -strengthened Co-base superalloys [14,15], which exhibited even better creep strength that was comparable to the Ni-base alloy IN100. The microstructural evolution of the high-temperature compressed samples has revealed that a slip of paired 1/2 o1 1 04 superpartial dislocations on the {0 0 1} planes in addition to the {1 1 1} planes in the γ 0 precipitates [2,3,16] results in flow stress anomalies at 700-800 1C. This dislocation movement mode is the same as that of the stress anomalies mechanism found in the γ 0 -Ni 3 Al compound [17,18].…”
Section: Introductionmentioning
confidence: 54%
“…In addition, strengthening of the grain boundaries by precipitates of borides or intermetallic phases has been found to be critical to the mechanical properties of the γ 0 -strengthened Co-base superalloys [14,15], which exhibited even better creep strength that was comparable to the Ni-base alloy IN100. The microstructural evolution of the high-temperature compressed samples has revealed that a slip of paired 1/2 o1 1 04 superpartial dislocations on the {0 0 1} planes in addition to the {1 1 1} planes in the γ 0 precipitates [2,3,16] results in flow stress anomalies at 700-800 1C. This dislocation movement mode is the same as that of the stress anomalies mechanism found in the γ 0 -Ni 3 Al compound [17,18].…”
Section: Introductionmentioning
confidence: 54%
“…For many different metals with the fcc structure, on which the L1 2 structure is based, the critical size has been reported to be in the range of 20-Scripta Materialia 121 (2016) 28-31 30 μm [12,17,18], while Uchic et al reported that the critical size for L1 2 -Ni 3 (Al,Ta) is 42 μm at room temperature [12]. However, this critical size value obtained for L1 2 -Ni 3 (Al,Ta) may not be used directly for L1 2 -Co 3 (Al,W), in view of the fact that the onset temperatures for yield stress anomaly are quite different for these two L1 2 compounds (77 K and 950 K respectively for Ni 3 (Al,Ta) [21] and Co 3 (Al,W) [4]). Cross slip of superpartial dislocations from (111) to (010) planes frequently occurs so as to give rise to yield stress anomaly even at room temperature for Ni 3 (Al,Ta), while such cross slip is unlikely to occur at room temperature for Co 3 (Al,W).…”
mentioning
confidence: 93%
“…Indeed, these γ + γ′ two-phase alloys called Co-based 'superalloys' have demonstrated superior high-temperature strength when compared to conventional Co-based alloys strengthened by solid-solution hardening and carbide precipitation without cuboidal γ′ precipitates [1-3]. We have recently investigated the deformation behavior of polycrystals of Co 3 (Al,W), the constituent phase of Co-based alloys, revealing that while the yield stress rapidly decreases with the increase in temperature at low temperatures, it increases anomalously with temperature only in a narrow temperature range at high temperatures (950-1100 K) [4,5]. TEM analysis has indicated that the yield stress anomaly is due to cross slip of superpartial dislocations with b (Burgers vector) = 1/2[ 101] from (111) to (010) planes [6,7] as in many other L1 2 intermetallic compounds based on Ni 3 Al, although these Ni 3 Al-based L1 2 intermetallic compounds are known to exhibit the yield stress anomaly in a much wider temperature range so as to start from a lower temperature such as liquid nitrogen temperature, especially in ternary alloys [8][9][10].…”
mentioning
confidence: 99%
“…Therefore, the measured APB energy is 71 mJ m −2 . For comparison, the {111} APB energy of Co 3 (Al,W) has been found to be 146 mJ m −2 [16], and in pure Ni 3 Al, 180 mJ m −2 [17]. In both systems, Ti and Ta are suspected to substantially raise the APB energy [17,18], but values of as low as 118 mJ m −2 are found in commercial superalloys, presumably because other alloying elements such as Cr decrease the APB energy.…”
Section: -P4 Eurosuperalloys 2014mentioning
confidence: 99%